Natural-product-inspired design and synthesis of thiolated coenzyme Q analogs as promising agents against Gram-positive bacterial strains: insights into structure–activity relationship, activity profile, mode of action, and molecular docking. Issue 32 (15th July 2022) - Yıldırım, Hatice; Yıldız, Mahmut; Bayrak, Nilüfer; Mataracı-Kara, Emel; Özbek-Çelik, Berna; Otsuka, Masami; Fujita, Mikako; Radwan, Mohamed O.; TuYuN, Amaç Fatih
Abstract : In an attempt to develop effective and potentially active antibacterial and/or antifungal agents, we designed, synthesized, and characterized thiolated CoQ analogs (CoQ1–8 ) with an extensive antimicrobial study. Abstract : In an attempt to develop effective and potentially active antibacterial and/or antifungal agents, we designed, synthesized, and characterized thiolated CoQ analogs (CoQ1–8 ) with an extensive antimicrobial study. The antimicrobial profile of these analogs was determined using four Gram-negative bacteria, three Gram-positive bacteria, and three fungi. Because of the fact that the thiolated CoQ analogs were quite effective on all tested Gram-positive bacterial strains, including Staphylococcus aureus (ATCC® 29213) and Enterococcus faecalis (ATCC® 29212), the first two thiolated CoQ analogs emerged as potentially the most desirable ones in this series. Importantly, after the evaluation of the antibacterial and antifungal activity, we presented an initial structure–activity relationship for these CoQ analogs. In addition, the most promising thiolated CoQ analogs (CoQ1 and CoQ2 ) having the lowest MIC values on all tested Gram-positive bacterial strains, were further evaluated for their inhibition capacities of biofilm formation after evaluating their in vitro potential antimicrobial activity against each of 20 clinically obtained resistant strains of Gram-positive bacteria. CoQ1 and CoQ2 exhibited potential molecular interactions with S. aureus DNA gyrase in addition to excellent pharmacokinetics and lead-likeness profiles. Our findings offer important implications for a potential antimicrobial drug candidate, in particular for the treatment of infections caused by clinically resistant MRSA isolates.